REVEALING CREATIVE ACCOUNTING PRACTICES: A PROFESSIONAL ETHICS PERSPECTIVE: Indonesia - Puspita Hardianti Anwar (ISAFIR: Islamic Accounting and Finance Review, 2022)
From the perspective of professional ethics, this study tries to look at the efforts made by auditors or accountants to find innovative accounting procedures. It is descriptive qualitative research that is being employed. This study examines the effectiveness of the auditor's professional code of ethics in identifying dishonest business practices. As the primary method for gathering data for this study, semi-structured interviews were used along with observation, documentation, and triangulation. The corporation constantly encounters different dangers known as business risk when doing its commercial activities. Fraud risk, which is categorized as an integrity risk, is included in this. The disclosure of innovative accounting techniques is governed by the accountant's code of ethics. It will be simpler for auditors to spot fraud if they possess integrity, objectivity, professional competence and accuracy, confidentiality, and professional demeanor. because they are truly aware of their responsibilities. also the dangers that would result from the auditor not disclosing the fraud. Keywords: Creative Accounting, Professional Ethics